Fostering justice across the Rio Conventions: Emerging levers for cooperation and coordination - Mariya Aleksandrova; Aparajita Banerjee; Marcelo Inácio da Cunha; Jean Carlo Rodríguez de Francisco; Michael Brüntrup; Daniele Malerba (German Institute of Development and Sustainability (IDOS), 2024)
The ever-deepening planetary crisis stipulates the urgency of bringing the Rio Conventions - the United Nations Framework Convention on Climate Change (UNFCCC), the Convention on Biological Diversity (CBD) and the United Nations Convention to Combat Desertification (UNCCD) - closer together to achieve common goals and overcome trade-offs. The 2024 meetings of the Conferences of the Parties (COPs), the supreme decision-making bodies of the Conven-tions, offer a window of opportunity towards that end. High-level political momentum was created with the official launch of the pioneering Rio Trio Initiative in the run-up of the three COPs in September to catalyse urgent collaboration between the three Rio Conventions to achieve sustainable futures for all. This Policy Brief explores entry points for enhanced cooperation and coordination with a focus on three emerging themes under the UNFCCC: nature-based solutions (NbS), loss and damage, and just transition pathways. In addition, we argue that the Rio Conventions offer multilateral and national platforms for integrating common justice principles (distributive, procedural, recognition, restorative, cosmopolitan, ecological) to meet shared goals across these three themes.
Keywords: 320; climate governance; loss and damage; nature-based solutions; just transition; environmental justice; social justice; climate finance; biodiversity; drought; land degradation